Sistem Informasi Problem Report Technical Support Pada PT. Bank Pembangunan Daerah Sumatera Selatan Dan Bangka Belitung Berbasis Website - Agustina Heryati; Darmawan Susilo; Iski Zaliman; Mulyati Mulyati; A Taqwa Martadinata; Candra Setiawan; Terttiaavini Terttiaavini (Jurnal Ilmiah Informatika Global, 2023)
PT Bank Sumsel Babel is one of the most developed regional banks in the archipelago. Bank Sumsel Babel also provides a variety of investment products, such as Depati, Demang, Telepathy, Pesirah Savings (Local Potential Activator), money transfers with Western Union, Debit Cards, export-import transactions, and ATM services. This research aims to help PT. Bank Sumsel Babel in dealing with technical support report problems. The current problem is that technical support reports independently and manually, causing delays and scattered reports. This reporting is the most important thing because the data is used for internal and external audit purposes and seeing the team's performance in solving the many problems that come in are all summarized in a monthly and annual report. Website problem report technical support is the best solution so that there are no delays in reporting and logs of solving problems that have been resolved can also be used by personal teams in solving new problems so that they can save time solving problems and a list of problem positions in open positions can be monitored by managers, administrators and the leader of the file section reports needed in audit requirements can be provided quickly.Keywords: Problem Report, Website, PT Bank Sumsel Babel